Space creation and restriction in elite soccer - Lames, M.; Siegle, M.; O`Donoghue, P. (World Congress of Performance Analysis of Sport IX, 2012)
Soccer matches involve two teams interacting as they contest the match. When one team has possession of the ball, the other team must compete to prevent scoring opportunities and to regain the ball. Therefore, many performance variables reflect one team`s attacking play and the other team`s defensive play. When in possession of the ball teams try to create space (Bangsbo and Peitersen, 2004) while the defending team tries to deny space (Bangsbo and Peitersen, 2002). The purpose of the current investigation was to determine if variables relating to space distinguish between possessions with different outcomes. Two types of data from the first half of a Bundesliga match were used in the current investigation; player position data generated by an automatic player tracking system and notation data for possession details. The first half of the match contained 107 possessions; there were 16 possessions that lead to a scoring opportunity (2 goals, 11 shots on target and 3 shots off target), 25 additional positions where the team in possession entered the attacking third and 66 possessions where they did not. A system was developed in Matlab version 7.1.0.246 (The Matworks Inc., Natick, MA) to determine mean distance variables from nearest opponents for the team in possession. This was done for the forward most 1 to 10 players in the team for the first and last 3s, 4s and 5s of possessions as well as the difference in mean space between the beginning and the end of the possessions. This gave a total of 90 (10 x 3 x 3) space variables that were compared between possessions of the 3 outcome types using a series of Kruskal Wallis H tests. There were no significant differences between possession types for space at the beginning of possessions (p > 0.05) or the difference in space between the beginning and end of possessions (p > 0.05). However, 8 of the 30 combinations of forward most player numbers and time at the end of possession were significantly different between the three types of possession (p < 0.05). The most significant variable was the mean space for the 10 outfield players during the final 5s of the possession (p = 0.007). The mean distance to the nearest opponent of 7.9+/-1.1m for possessions that did not enter the attacking third and the 7.6+/-1.1m for those that did were both significantly greater than when possessions lead to a scoring opportunity (p < 0.05). The mean distance to the nearest opponent was 7.5+/-1.4m during the last 5s when the 2 goals were scored, 6.4+0.8m when there was a shot on target and 6.1+/-0.2m when there was a shot off target. This variable may be a useful indicator one team`s ability to create space when in possession and another team`s ability to restrict space when defending.